(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Performance management in the modern public sector organisations is the use of interrelated strategies and activities to improve the performance of individuals, teams and organisations. Performance management is an essential tool that is relevant at all levels in all public sector organisations. It provides a means to improve organisational performance by linking and aligning individual, team and organisational objectives and results. It also provides a means to recognise and reward good performance and to manage under-performance.This article explores the effects of performance management and development on modern public sector organisations including factors that limit the implementation of such measures in the promotion and retention of staff. Performance management in the modern public sector organisations can be described as work in progress. Significant progress has been made but major challenges remain, especially on the issues of credibility and staff engagement.